Revelation as the Thou of Jesus Christ Joseph Ratzinger’s/Pope Benedict XVI’s Contribution to a deeper Understanding of Revelation - de Gaál, Emery (Poznańskie Studia Teologiczne, 2016)
The article discusses Pope Benedict XVI’s / Joseph Ratzinger’s understanding of revelation. It shows the bases for his understanding to be found in the theology of St. Bonaventure, more specifically in the Doctor Seraphicus’ Hexaëmeron. It is on the theology of history in Bonaventure that Ratzinger had written his terminal paper. This will allow him to impact Vatican II in an original way. The essay describes how the young peritus Joseph Ratzinger contributed in a most decisive way to the dogmatic constitution on divine revelation Dei Verbum’s recalibration of the nature of revelation. It also discusses hope Pope Benedict‘s teaching office thematized revelation. Revelation is ultimately neither Scripture nor tradition, but the self-disclosure of the Triune God in the Thou of Jesus Christ.